22. STUDY OF WORK MOTIVATION OF MEDICAL STAFF AT VINMEC TIMES CITY HOSPITAL, HANOI IN 2024 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the working motivation of medical staff at various clinical departments of Vinmec Times City International General Hospital, Hanoi, in 2024 and to analyze related factors.Research objects and methods: Data were collected from 288 doctors working at the hospital using cross-sectional descriptive method and a self-completed questionnaire with a 5-level Likert scale.Results: The overall average score of medical staff with good work motivation is 4,04 (maxiumum score of 5). The highest score was for the nature of work (average 4.17 points), while the lowest score was for motivation from recognition of achievements (average 3.85). Medical staff who are satisfied with the policy and administration regime have a significantly higher level of good motivation compared to those who are not satisfied (PR = 2.01; p = 0.001). Similarly, medical staff satisfied with work management and supervision have a higher rate of good motivation than those who are not satisfied (PR = 1.32; p = 0.001). Additionally, medical staff with positive attitudes about hospital suggestions show higher motivation levels than those with negative attitudes (PR = 1.69; p = 0.001).Conclusion: The percentage of employees with high work motivation is quite substantial. Factors significantly related to work motivation include satisfaction with the hospital's management regime, positive attitudes towards management, and alignment with personal aspirations and benefits (salary, bonuses, and welfare). Professional qualifications, career development opportunities, and a positive attitude towards providing feedback to the hospital are also related to employee motivation.
Keywords: Động lực làm việc; nhân viên y tế; Bệnh viện Đa khoa quốc tế Vinmec Times City